Domestic work in Cape Town: an exploration into the growth of part-time domestic work - Wooldridge, Kathryn (Department of Sociology, 2021)
Statistical analysis of the labour market in South Africa shows that between 1994 and 2015, the growth rate of domestic worker employment was slow in comparison to the growth rate of high-income jobs. In Gauteng, the slow growth of domestic worker employment contributed to the overall slow growth of all unskilled jobs. This is because domestic workers consist of around half of all unskilled jobs. The growth of these elementary jobs was therefore much slower compared to high-income middle-class jobs (Crankshaw, forthcoming). Therefore, Gauteng experienced professionalisation rather than social polarisation. Like Gauteng, Cape Town has also experienced professionalisation, due in part to the slow growth of domestic worker employment. The slow growth of domestic worker employment can be partly attributed to the growth of part-time domestic worker employment. This is because households employing part-time domestic workers tend to share domestic workers, which leads to fewer domestic workers being employed per household (Crankshaw, forthcoming). This thesis explores some of the reasons behind the growth of part-time domestic work in Cape Town. Specifically, it uncovers and describes some of the reasons behind why middleclass households in Cape Town choose to employ part-time domestic workers. The thesis also explores how legislation has an impact on the wages, hours, and conditions of employment of domestic workers in middle-class households. The research conducted for this thesis uses both descriptive statistical methods and qualitative methods. The statistical research lays the foundation for the qualitative research by showing the slow growth rate of domestic employment in comparison to managerial, professional, and technical occupations. A critical realist approach is used to guide the qualitative research. A critical realist approach seeks to explain causality through understanding the qualitative properties which create, determine or generate relations and objects. Therefore, the qualitative research uncovers and describes some of the causal mechanisms behind the growth of part-time domestic work in Cape Town with a specific focus on middle-class households. Reasons behind why middleclass households employ full-time domestic workers or no domestic workers at all, is explored as counterfactual evidence. The thesis finds that many middle-class households which hire domestic workers do not base their wages only on the minimum wage. Rather the wages these households set are influenced more by their personal values and/or personal finances. The households in this study which employed domestic workers did not generally adhere to government regulations such as having written contracts with their domestic workers or registering them for UIF. The causal mechanisms behind the decision to hire part-time, full-time or no domestic work is summarised in the table below. Shared causal mechanisms are highlighted.